Benedictine Living : Reflections for Prayer and Meditation - Ritger, Kate (Book collections on Project MUSE., 2014)
Open up your everyday experiences by considering them through a Benedictine lens with this accessible collection of reflections. Meaningful and insightful at any time of the year, this companion offers Benedictine and scriptural wisdom to the timeless themes of our lives.